CCR5Δ32 and the genetic susceptibility to rheumatoid arthritis in admixed populations: a multicentre study. - Toson, Bruno; Dos Santos, Eduardo José; Adelino, José Eduardo; Sandrin-Garcia, Paula; Crovella, Sergio; Louzada-Júnior, Paulo; Oliveira, Renê Donizete Ribeiro; Pedroza, Larysse Santa Rosa Aquino; de Fátima Lobato Cunha Sauma, Maria; de Lima, Clayton Pereira Silva; Barbosa, Fabiola Brasil; Brenol, Claiton Viegas; et al. (Rheumatology (Oxford), 2017)
Keywords: Arthritis, Rheumatoid; Brazil; Case-Control Studies; Consanguinity; Gene Frequency; Genetic Predisposition to Disease; Humans; Polymorphism, Single Nucleotide; Receptors, CCR5

Ficolin Gene Polymorphisms in Systemic Lupus Erythematosus and Rheumatoid Arthritis. - Addobbati, Catarina; De Azevêdo Silva, Jaqueline; A C Tavares, Nathália; Monticielo, Odirlei; M Xavier, Ricardo; T Brenol, João Carlos; Crovella, Sergio; B Chies, José Artur; Sandrin-Garcia, Paula (Ann Hum Genet, 2015)
Systemic lupus erythemathosus (SLE) and rheumatoid arthritis (RA) are complex autoimmune diseases characterized by an immune balance breakdown and by chronic inflammation. Several findings link SLE and RA development with the complement system and ficolin components have emerged as candidates for disease development. Since genetic association studies with ficolin genes in SLE and RA have not yet been conducted in a Brazilian population, the aim of this study was to determine whether polymorphisms of ficolin-1(FCN1) and ficolin-2 (FCN2) genes are associated with SLE and RA susceptibility as well as disease manifestation. Two SNPs within FCN1 (rs2989727 and 1071583) and three in FCN2 (rs17514136, rs3124954, and rs7851696) were studied in 208 SLE and184 RA patients as well as 264 healthy individuals in a Southeast Brazilian population. For SLE patients, the FCN2 rs17514136 SNP was associated with a more severe disease (SLICC) (p = 0.0067). Furthermore, an association between the occurrence of nephritis and the T/T genotype for FCN2 rs3124954 SNP (p = 0.047, OR = 3.17, 95%CI = 1.34-7.5) was observed. No association was observed between the studied polymorphisms and RA development. Thus, our data support involvement of the FCN2 gene in the SLE phenotype.

Vitamin D receptor polymorphisms and expression profile in rheumatoid arthritis brazilian patients. - Cavalcanti, Catarina Addobbati Jordão; De Azevêdo Silva, Jaqueline; de Barros Pita, Will; Veit, Tiago Degani; Monticielo, Odirlei Andre; Xavier, Ricardo Machado; Brenol, João Carlos Tavares; Brenol, Cleiton Viegas; Fragoso, Thiago Sotero; Barbosa, Alexandre Domingues; Duarte, Ângela Luiza Branco Pinto; Oliveira, Renê Donizeti Ribeiro; et al. (Mol Biol Rep, 2015)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation and important joint commitment, being the most common systemic autoimmune disease worldwide. RA displays important genetic background with a variety of genes contributing to the immune balance breakdown. Recent studies have demonstrated that vitamin D, through its receptor (VDR), is able to regulate the immune balance and suppress the autoimmunity process, being a potential target in autoimmune diseases. In the present genetic association study, we assessed 5 Tag single nucleotide polymorphisms (SNPs) (rs11168268, rs2248098, rs1540339, rs4760648 and rs3890733), which cover most of the VDR gene, in three different Brazilian populations (from Northeast, Southeast and South Brazil). We also evaluated the VDR expression profile in whole blood and monocytes from RA patients. For genotyping study, 428 RA patients and 616 healthy controls were genotyped with fluorogenic allele specific probes on an ABI7500 platform. For gene expression study, VDR mRNA levels of 15 RA patients and 26 healthy individuals were assessed by RT-PCR. Our results showed that SNPs rs4760648 and rs3890733 are associated to RA susceptibility (p value = 0.0026, OR 1.31 and p value = 0.0091, OR 1.28 with statistical power = 0.999 and 0.993, respectively). Regarding RA clinical features, the studied SNPs did not show significant associations. The gene expression assays showed that VDR mRNA levels were down regulated in both whole blood (-3.3 fold) and monocytes (-3.2 fold) of RA patients when compared to healthy controls. Our results, the first reported for distinct Brazilian populations, support a role of the VDR gene in the susceptibility to RA.

LIG4 and RAD52 DNA repair genes polymorphisms and systemic lupus erythematosus. - De Azevêdo Silva, Jaqueline; Pancotto, João Alexandre Trés; Donadi, Eduardo Antônio; Crovella, Sergio; Sandrin-Garcia, Paula (Mol Biol Rep, 2014)
Systemic lupus erythematosus (SLE) is a complex autoimmune disorder with a strong genetic background. Nevertheless, SLE might also be triggered due to environmental factors, such as UV light exposure. DNA double strand breaks (DSBs) may be induced secondarily by UV radiation, increasing DNA immunogenicity and in SLE patients DNA repair is diminished, allowing the accumulation of DSBs and genomic instability. LIG4 and RAD52 genes play important roles in DNA repair mechanisms and a recent microarray analysis showed their differential expression in active SLE patients. In this study we investigated a potential association between LIG4 and RAD52 single nucleotide polymorphisms (SNPs) and SLE predisposition in a Southeast Brazilian population. We assessed four Tag SNPs in LIG4 and three in RAD52 gene region, encompassing most of the gene sequence, in 158 SLE patients and 212 healthy controls. We also performed SNPs analysis considering clinical manifestation, gender and ethnicity in SLE patients. Our data did not show association between LIG4 and RAD52 SNPs and SLE, its clinical manifestations or ethnicity in the tested population. The analysis regarding ethnicity and SLE clinical manifestations indicated Caucasian-derived patients as more susceptible to cutaneous and hematological alterations than the African-derived. To our knowledge, this is the first association study involving LIG4 and RAD52 genes and SLE predisposition.
Keywords: Adult; Alleles; Brazil; Case-Control Studies; DNA Ligases; DNA Repair; Ethnic Groups; Female; Genetic Linkage; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Lupus Erythematosus, Systemic; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide; Rad52 DNA Repair and Recombination Protein

Polimorphisms in inflammasome genes are involved in the predisposition to systemic lupus erythematosus. - Pontillo, Alessandra; Girardelli, Martina; Kamada, Anselmo J; Pancotto, Joao A T; Donadi, Eduardo A; Crovella, Sergio; Sandrin-Garcia, Paula (Autoimmunity, 2012)
Recent findings provide evidence of inflammasome critical role in the predisposition to autoimmune disorders. The involvement of inflammasome in the pathogenesis of systemic lupus erythematosus (SLE) has been hypothesized even if no significant association within inflammasome genes mutations or polymorphisms and lupus has been reported yet. We analyzed 14 single nucleotide polymorphisms (SNPs) within 7 inflammasome genes (NLRP1, NLRP3, NLRC4, AIM2, CARD8, CASP1, IL1B) in 144 patients affected by systemic lupus erythematosus and in 158 healthy controls from Southern Brazilian (state of São Paulo) with the aim of disclosing the possible role of inflammasome genes in the susceptibility of SLE. Our results demonstrated that NLRP1 rs2670660 SNP and the NLRP1 rs12150220-rs2670660 A-G haplotype were associated with SLE in our study population, and in particular with the development of nephritis, rash and arthritis. These findings are concordant with previously reported association of NLRP1 with vitiligo and type-1 diabetes underlining once more the involvement of NALP1 inflammasome in the pathogenesis of autoimmune disorders.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Alleles; Apoptosis Regulatory Proteins; Brazil; Female; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Inflammasomes; Lupus Erythematosus, Systemic; Male; Middle Aged; Polymorphism, Single Nucleotide

Mannose binding lectin gene (MBL2) functional polymorphisms are associated with systemic lupus erythematosus in southern Brazilians. - Sandrin-Garcia, Paula; Brandão, Lucas André Cavalcanti; Coelho, Antônio Victor Campos; Guimarães, Rafael Lima; Pancoto, João Alexandre Trés; Segat, Ludovica; Donadi, Eduardo Antônio; de Lima-Filho, José Luiz; Crovella, Sergio (Hum Immunol, 2011)
Susceptibility to systemic lupus erythematosus (SLE) has been associated with immunologic, environmental, and genetic factors. To uncover a possible association between MBL2 gene polymorphisms and SLE, we analyzed functional polymorphisms in the promoter and first exon of the MBL2 gene in 134 Brazilian SLE patients and 101 healthy controls. Genotype and allele frequencies of MBL2 A/O polymorphism were significantly different between patients and controls, and the O allele was associated with an increased risk of SLE. An association between low mannose binding lectin (MBL) producer combined genotypes and increased risk for SLE was also reported. Furthermore, when stratifying SLE patients according to clinical and laboratory data, an association between the A/O genotype and nephritic disorders and between the X/Y genotype and antiphospholipid syndrome was evident. Combined genotypes responsible for low MBL production were more frequently observed in SLE patients with nephritis. Our results indicate MBL2 polymorphisms as possible risk factors for SLE development and disease-related clinical manifestations.
Keywords: Adolescent; Adult; Aged; Brazil; DNA Mutational Analysis; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Lupus Erythematosus, Systemic; Male; Mannose-Binding Lectin; Middle Aged; Polymorphism, Genetic; Population Groups; Promoter Regions, Genetic